2021
DOI: 10.7240/jeps.875709
|View full text |Cite
|
Sign up to set email alerts
|

Metal Oksit Nanopartiküllerin Genotoksik Etkileri

Abstract: Nanopartiküller (NP) (Nanomateryaller-NM), hızla gelişen nanoteknolojide çığır açan partiküllerdir. Bu partiküllerin en az bir boyutu 1-100 nm aralığındadır. Metal oksit nanopartikülleri, nanomateryallerin temel üyelerinden biri olup, tıp, kozmetik, boya, tekstil ve gıda ürünleri gibi çok çeşitli alanlarda yaygın bir şekilde kullanılmaktadır. Metal oksit NP’lerinin yoğun kullanımı, insanların partiküllere inhalasyon, dermal ve oral yollar dahil çeşitli yollarla maruz kalmasına sebep olmaktadır. Diğer taraftan,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 111 publications
(149 reference statements)
0
2
0
Order By: Relevance
“…It has been reported that factors such as metal ions released from the surface of metal NPs, which have various antimicrobial activity properties, reportedly induce the vast majority of bacteria to cause infection and antimicrobial activity 41 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that factors such as metal ions released from the surface of metal NPs, which have various antimicrobial activity properties, reportedly induce the vast majority of bacteria to cause infection and antimicrobial activity 41 …”
Section: Resultsmentioning
confidence: 99%
“…36,40 It has been reported that factors such as metal ions released from the surface of metal NPs, which have various antimicrobial activity properties, reportedly induce the vast majority of bacteria to cause infection and antimicrobial activity. 41 The use of plant extracts has the potential to replace traditional chemical and physical methods for NP production. In particular, plant-mediated biosynthesis has become increasingly important due to its flexibility and environmentally friendly nature.…”
Section: Cytotoxic Activitymentioning
confidence: 99%